Clinical update on inflammatory disorders of the gastrointestinal tract - Mayerle, Julia 1973-; Tilg, Herbert 1962- (Karger, 2010)
Digestive-disease-associated mortality accounts for a major part of all deaths in Western societies and inflammatory diseases such as GI infections, viral hepatitis, GERD or cancers due to chronic inflammation have a tangible economic and social impact. What further aggravates the situation is the fact that complex immunological disorders have surfaced where anti-infective treatments are not effective. Fortunately, due to breakthroughs in basic research that are being successfully translated into clinical practice, new treatment strategies are constantly evolving. In addition to the development of new therapeutic measures, however, it is also mandatory to review and periodically refine established treatment regimens to reflect current knowledge and ensure up-to-date medical care.Combining outstanding basic research reviews with cutting-edge treatment guidelines on inflammatory disorders of the GI tract, this book presents newly identified treatment targets and provides clinicians and practitioners in the field with a most useful account of the state of the art
A summary of the state of the art
Keywords: Gastrointestinale Krankheit; Chronische Darmentzündung; Entzündung; Aufsatzsammlung